Marine Debris Collection Model with Intermediate Transition Station (ITS) Systems Planning in Jakarta - Mega Mutiara Sari; Takanobu Inoue; Regil Kentaurus Harryes; Iva Yenis Septiariva; Kuriko Yokota; Suprihanto Notodarmodjo; Shigeru Kato; Kevin Foggy Delu; Wisnu Prayogo; I Wayan Koko Suryawan (Jurnal Ilmu Lingkungan, 2024)
Marine debris in Jakarta is a complex problem because the amount is too large every day. Addressing this critical gap, this study proposes a model for efficient waste transportation through the development of an Intermediate Transition Station (ITS) system. This system not only facilitates the effective movement of waste but also incorporates a recovery process to reduce the volume of debris before it reaches the landfill. The ITS serves as a pivotal node in the waste management network, ensuring the continuity of waste flow from accumulation points to processing facilities. With the ITS, the total marine debris managed amounts to 39.96 tons/day, of which 9.33 tons/day is recovered, leaving a significantly reduced residue of 25.63 tons/day or 1.134 m3/day for landfill disposal. Implementing the Haul Container System (HCS) within this framework, the study demonstrates that waste transportation from the ITS to Jakarta's Bantar Gebang Integrated Waste Processing Site can be streamlined to just 3 trips/day. By providing a structured and strategic approach to marine debris transportation, the ITS model aims to prevent the re-pollution of Jakarta's water bodies and significantly reduce the carbon footprint by 67.2% from current conditions, thereby offering a sustainable solution to this pressing urban environmental challenge.